Chondromalacia patella increases the risk of herpes zoster: a population-based study - Chia-Hung Chen; Yung-Chi Cheng; Hsin-Yi Yang; Ching-Fang Tsai; Chao-Yu Hsu; Der-Shin Ke; Wen-Che Hsieh (BMC Musculoskeletal Disorders, 2022)
Abstract Background The reactivation of herpes zoster (HZ) is associated with disease stress. However, the relationship between chondromalacia patella (CMP) and HZ remains poorly understood. This study investigated the relationship between CMP and the risk of developing HZ. Methods Data were collected from the Taiwan’s National Health Insurance Research Database. Patients with CMP diagnosed between 2000 and 2017 were assigned to the case group; patients without CMP were randomly selected from the same database and paired with controls matched by age and sex. The primary outcome was a diagnosis of HZ. All patients were followed until their diagnosis of HZ, their withdrawal from the NHI program, their death, or the end of 2017, whichever was earliest. The risk of developing HZ was compared between the case and control groups. Results In total, 22,710 patients with CMP and 90,840 matched controls were enrolled. The overall incidence rates of HZ in the CMP and control cohorts were 7.94 and 7.35 per 1,000 person-years, respectively. After potential confounders were controlled for, the case group exhibited a higher risk of HZ than did the control group [adjusted hazard ratio (aHR) = 1.06, p < 0.05]. In a stratification analysis by age, patients over 65 years old in the CMP group exhibited a higher risk of HZ than did those in the control group (aHR = 1.22, p < 0.01). In a stratification analysis by sex, women with CMP were at greater risk of developing HZ than women without CMP (aHR = 1.18, p < 0.01). Conclusion Patients with CMP, especially elder adults and women, exhibited a higher risk of HZ. The HZ risk of patients with CMP should thus be assessed, and the necessity of HZ vaccination should be informed.